2017
DOI: 10.5334/tohm.348
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Botulinum Toxin on Network Connectivity in Cervical Dystonia: Lessons from Magnetoencephalography

Abstract: Background: Pharmacological management of cervical dystonia (CD) is considered to be symptomatic in effect, rather than targeting the underlying pathophysiology of the disease. Magnetoencephalography (MEG), a direct measure of neuronal activity, while accepted as a modality for pre-surgical mapping in epilepsy, has never been used to explore the effect of pharmacotherapy in movement disorders. Methods: Resting state MEG data were collected from patients with CD, pre-and post-botulinum toxin injections. All of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Our previous study assessing changes in coherence using resting state had shown that compared to controls, CD patients showed a state of lower amplitude and frequency of synchronicity, and a lower frequency of synchronicity of oscillating neurons, or coherence [ 9 ]. With task specific testing, controls showed increased coherence in one pathway involving the cingulate gyrus, associated with decision-making.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study assessing changes in coherence using resting state had shown that compared to controls, CD patients showed a state of lower amplitude and frequency of synchronicity, and a lower frequency of synchronicity of oscillating neurons, or coherence [ 9 ]. With task specific testing, controls showed increased coherence in one pathway involving the cingulate gyrus, associated with decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is also the first to assess the effect of botulinum toxin treatment on network connectivity while performing a task assessing executive function using MEG-CSI. Previously, we showed that efficacious botulinum toxin use is associated with a change in coherence in specific pathways in the resting state, suggesting a role of sensorimotor integration in clinical benefit [ 9 ]. Our current study shows a statistically significant change in coherence, albeit small, during the visual CPT in CD patients with botulinum injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Our lab has also previously published work on cervical dystonia using MEG-CSI. 10,11 In the present study, we characterized the functional connectivity in a patient with ED where touch is used to evoke dystonic movements.…”
Section: Introductionmentioning
confidence: 99%